The influence of some tumor characteristics on the long-term survival of proximal colorectal cancer patients - Ratsiborskyi, D.; Mashukov, A. (Journal of Education, Health and Sport, 2024)
The article is devoted to the study of survival in colorectal cancer and the influence of some common clinical factors on the life expectancy. Colorectal cancer (CRC) is an urgent problem of today and modern oncology, as the incidence of CRC is constantly increasing. It is believed that the development of CRC in 50% of all cases is related to lifestyle and long-term exposure to carcinogens. Genetic factors play a decisive role in 5 to 20% of cases. It has been established that from 20 to 50% of patients with CRC already have distant metastases at the initial presentation. The understanding of the biology of colon cancer is based on the analysis of the degree of aggressiveness of its course, patient survival, the effect of performed operative and combined treatment methods on the course of the disease, and the presence of some other factors that are not yet completely understood by clinicians (the influence of hidden metastasis, circulating cancer cells, genetic causes, etc.). Proximal colon tumors are tumors that located in the cecum, ascending, and hepatic flexure of the colon, that is, in fact, tumors of the right half of the colon. The more proximally the tumor was located in the right half of the colon, the longer the patients lived. At a follow-up period of 24 months, the duration of follow-up for patients with cecum, ascending colon, and hepatic angle tumors was 71.43%, 63.64%, and 72.73%, respectively. For the observation period of 32 months: 42.86%, 36.36%, 18.18%. For the observation period of 55 months: 14.29%, 9.09%, 0%, respectively. Thus, biology was the key factor, as the groups were equivalent in terms of stage, frequency of lymph node involvement, and degree of tumor differentiation. Therefore, from our point of view, the separation of right-sided RTK, r-RTK into a apparant nosoform has a clinically significant character: it is in the right half of the colon that the toxicoanemic form occurs more often; and less often (almost never) – obturation, much more characteristic of left-sided cancer, l-RTK. Typically, right-sided colon tumors have the following genomic context: MLH1 hypermethylation, BRAF mutation, and high-grade MSI, while left-sided colon tumors are p53 and KRAS mutant.